Paradigma Pendidikan Islam Multikultural: Studi Epistemologi Humanis Emansipatoris Dalam Pemikiran Nurcholish Madjid - Muhamad Takrip; Munir; Ismail; Anis Ma`rifatul Mustofiyah (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2025)
his study explores the integration of humanist-emancipatory epistemology in Islamic multicultural education based on the thought of Nurcholish Madjid. In a pluralistic society, education should not merely transfer knowledge but also develop human dignity, moral sensitivity, and critical thinking. Humanist education emphasizes the balance between intellect and spirit, fostering freedom of thought, equality, and respect for diversity. By integrating multicultural values, contextualized interpretation of the Qur’an, and participatory learning, Islamic education cultivates students who are not only intellectually capable but also socially responsible and ethically conscious. This study uses qualitative literature research, analyzing primary and secondary sources to identify key concepts and patterns related to humanist, inclusive, and multicultural educational practices. The findings highlight that humanist-emancipatory education encourages holistic development, gender equality, and active engagement with societal diversity, empowering students to contribute meaningfully to a just, peaceful, and pluralistic society.